The Effect of Teacher Autonomy on Assessment Practices among Malaysian Cluster School Teachers - Varatharaj, Ravikumar; Abdullah, Abdul Ghani Kanesan; Ismail, Aziah (International Journal of Asian Social Science, 2015)
Teacher autonomy has become an important aspect of the teacher professionalism. An autonomous teacher while able to produce autonomous learners are also able to be independent implementers of government policies in particular education policies. Therefore the aim of this quantitative study is examine the perception of teacher autonomy among the Cluster School teachers, and its’ effect on their assessment practices. Data for this study were obtained from randomly selected 471 trained teachers from all Malaysian Cluster Schools. The findings reveled that teacher autonomy and assessment practices are at moderately level respectively. Meanwhile findings also indicate that only teacher autonomy dimension of curriculum autonomy possess a significant effect on assessment practices in terms of explicit learning, students autonomy, and student performance. Finally implications and contributions of the study were also discussed.